Application of Organic Fertilizer from Rabbit and Cattle Farm Waste on the Growth and Yield of Chili peppers (Capsicum annuum L.) - Mahardika, Ida Bagus Komang; Wirajaya, Anak Agung Ngurah Mayun; Arjana, I Gusti Made (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Chili peppers are one of the important vegetable commodities for the community both in terms of economic value and nutritional content. This study aims to determine the effectiveness of providing organic fertilizers from rabbit farm waste combined with organic fertilizers from cattle farm waste on the growth and yield of chili pepper plants. The study was conducted using an experimental method, with the experimental design used being a factorial Randomized Block Design with 3 replications. There were two factors studied, namely: the dose of Rabbit Farm Waste Fertilizer (R) consisting of 3 levels and the dose of Cattle farm waste fertilizer (C) consisting of 3 levels. Each type of fertilizer treatment consisted of 3 levels, namely: 0 ton/ha; 10 tons/ha; 20 tons/ha. The results of this study indicate that rabbit manure has a significant effect, especially on the oven dry weight of fruit, the number of fruits, and the fresh weight of harvested fruit, as well as the dry weight of the stove. Meanwhile, cow manure significantly affects plant height and fresh weight of the stover and has a very real effect on other variables. The highest oven dry weight of harvested fruit per plant was obtained in the rabbit manure treatment of 30 tons/ha, which was 26.68 g, which was 78.3% higher than the lowest in the treatment of 0 tons/ha, which was 14.98 g. Meanwhile, the highest oven-dry weight of fruit per plant was in the cow manure treatment at a dose of 30 tons/ha, which was 34.07 g, which increased by 151.1% with the lowest treatment of 0 tons/ha, which was 13.56 g. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero Hunger SDG 3: Good Health and Well-being SDG 12: Responsible Consumption and Production SDG 13: Climate Action SDG 15: Life on Land